Modeling and Experiment on Active Magnetic Bearing as Force Actuators to Detect Inner Race Fault of Rolling Element Bearing - Yuanping Xu; Jin Zhou; Chaowu Jin, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
As one of the important components in the rotating machinery, the condition of rolling element bearing has a great impact on the system performance. Therefore, the fault detection for the rolling element bearing is important and many methods have been proposed. Following our previous work on the outer race defect diagnosis, in this paper, the active magnetic bearing (AMB) is employed as an exciter to apply electromagnetic force to detect the inner race defects. The theoretical model of a nonlinear bearing-pedestal system model with the inner race defect under the electromagnetic force is developed and investigated. The simulation and experimental results show that the characteristic signal of inner race defect is amplified under the electromagnetic force through the AMBs, which is helpful for improving the diagnosis accuracy.